2014
DOI: 10.1101/gad.243121.114
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis-dependent stabilization of Bre1 fine-tunes histone H2B ubiquitylation to regulate gene transcription

Abstract: Monoubiquitylation of histone H2B on Lys123 (H2BK123ub1) plays a multifaceted role in diverse DNA-templated processes, yet the mechanistic details by which this modification is regulated are not fully elucidated. Here we show in yeast that H2BK123ub1 is regulated in part through the protein stability of the E3 ubiquitin ligase Bre1. We found that Bre1 stability is controlled by the Rtf1 subunit of the polymeraseassociated factor (PAF) complex and through the ability of Bre1 to catalyze H2BK123ub1. Using a doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Subsequent genetic and biochemical studies in yeast have shown that Rtf1 functions as a component of the polymerase-associated factor 1 (Paf1) complex (PAF1C) containing Paf1, Ctr9, Leo1, and Cdc73 (2)(3)(4)(5). The PAF1C is a multifunctional protein complex whose primary role is to facilitate histone modifications, such as H2B monoubiquitination at K123 and H3 methylation at K4 and K79 (6)(7)(8)(9)(10)(11)(12). The PAF1C also plays important roles in transcription elongation through chromatin, as well as on naked DNA (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Subsequent genetic and biochemical studies in yeast have shown that Rtf1 functions as a component of the polymerase-associated factor 1 (Paf1) complex (PAF1C) containing Paf1, Ctr9, Leo1, and Cdc73 (2)(3)(4)(5). The PAF1C is a multifunctional protein complex whose primary role is to facilitate histone modifications, such as H2B monoubiquitination at K123 and H3 methylation at K4 and K79 (6)(7)(8)(9)(10)(11)(12). The PAF1C also plays important roles in transcription elongation through chromatin, as well as on naked DNA (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…We hypothesize that the HMD serves as a cofactor in the H2B ubiquitylation process by enhancing the ability of Bre1 to direct Rad6 to the appropriate lysine on H2B and/or by stimulating the catalytic ability of Rad6 in the presence of Bre1. This hypothesis does not exclude additional roles for Rtf1 or other Paf1C subunits in facilitating recruitment of Rad6-Bre1, stimulating H2Bub by an effect on elongation, or stabilizing Bre1 at the protein level (Wozniak and Strahl, 2014). Our results provide mechanistic insight into a crucial histone modification pathway.…”
Section: Discussionmentioning
confidence: 99%
“…An antibody against human H2B K120ub (Cell Signaling #5546; 1:1000 dilution) was used to detect H2B K123ub in yeast (Wozniak and Strahl, 2014). Lack of antibody reactivity in H2B K123R and bre1Δ mutant strains confirms specificity of the antibody for the appropriate lysine.…”
Section: Methodsmentioning
confidence: 99%
“…RNF20/RNF40 exists as a tetramer containing two copies of each protein (25). They are reported to be required for the transcription of some genes (2628), and play vital roles in some fundamental biological processes such as stem cell differentiation (2931) and tumorigenesis (26,32). Whether H2Bub or its related E3 ligase involved in meiotic recombination or spermatogenesis in mammals is unknown.…”
Section: Introductionmentioning
confidence: 99%